Double-lumen tubes verus single-lumen tube in patients undergoing minimally invasive cardiac surgery: a randomised, controlled clinical trial - Wang, Zhenzhong; Zhao, Junfei; Ke, Yingjie; Wang, Qiuji; Li, Yuxin; Ye, Yingxian; Zhang, Jianjun; Guo, Xiaogang; Zeng, Qingshi; Huang, Huanlei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundOne-lung ventilation (OLV) with double-lumen tubes (DLT) are prone to complications such as airway injury and hypoxemia. It is not clear whether a two-lung ventilation (TLV) with single-lumen tube (SLT) is beneficial for patients undergoing totally endoscopic cardiac valve surgery (TECVS).MethodsWe conducted a pragmatic, single-centre, single-blinded randomised controlled trial. Patients (aged ≥18 years) who underwent total endoscopic cardiac valve surgery were randomly assigned to a DLT group or a SLT group. A two-week telephone follow-up was conducted. The oxygenation index (PaO2/FiO2) was the primary outcome. The secondary outcomes included PaCO2, postoperative intubation complications, postoperative pulmonary complications and airway injury.ResultsA total of 220 patients were randomly assigned. After randomisation, 20 patients were excluded, leaving 100 patients in each of the two groups. The PaO2/FiO2 were significantly greater in the SLT group than in the DLT group (P < 0.001). The incidence of postoperative intubation adverse events, postoperative pulmonary atelectasis, and hoarseness was significantly lower in the SLT group (P < 0.001, P = 0.029 and P = 0.028, respectively). The pre-exposure time and intubation time were shorter in the SLT group (both P values < 0.001). We used t test, Mann-Whitney U test and Fisher's exact test to account the difference of perioperative and follow-up outcomes.ConclusionsTwo-lung ventilation with single-lumen tube is easy to perform, significantly increases oxygenation, and decreases the incidence of postoperative complications and airway injuries. Advantages remain especially for patients with preoperative pulmonary dysfunction.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=165709, identifier [ChiCTR2200066822]. Date: 19/12/2022.